(untitled) (Indian Journal of Arid Horticulture, 2025)
Water is one of the precious input on which productivity of vegetable crops depends. However the precious input is scarcity available in hot arid areas of Rajasthan. Besides rain water, both surface and ground water being used for vegetable production. The water is applied to the plants either through gravity flow system or pressurized irrigation system. It is estimated that the efficiency of canal irrigation system is about 40% resulting in wastage of water with low application efficiency. Therefore, a field experiment on the use of drip irrigation system with and without mulches was conducted during the year 2006 & 07 in the rainy season at research farm of COA, SKRAU, Bikaner. There were four volume of water and three mulches were used singly and in their possible combination. The maximum length of fruit and number of fruits were observed with the treatment of drip 0.70 V and among the mulches these parameters were higher under organic mulch. The maximum fruit yield was recorded with application of 0.70 V of water and with organic mulch singly and in combined form.